2016
DOI: 10.18632/oncotarget.7531
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-27b up-regulated by human papillomavirus 16 E7 promotes proliferation and suppresses apoptosis by targeting polo-like kinase2 in cervical cancer

Abstract: The infection with high-risk human papillomavirus is linked to cervical cancer, nevertheless, the role of miRNAs regulated by HPV oncogenes in cancer progression remain largely unknown. Here, we knocked down endogenous E6/E7 in HPV16-positive CaSki cell lines, screened differences in miRNA expression profile with control using miRNA array. 38 miRNAs were down-regulated and 6 miRNAs were up-regulated in the E6/E7 silenced CaSki cells (>2-fold changes with P <0.05). The levels of miR-27b, miR-20a, miR-24, miR-93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 39 publications
2
46
0
Order By: Relevance
“…These E6/E7 oncoproteins have been shown to upregulate A3B (a major mutagenic protein) expression in HPV-induced tumorigenesis [53]. Other proteins, such as KLF13 and DGCR8, have also been implicated in HPV-induced tumorigenesis [54, 55]. In this study, aberrant KIF20A protein expression was observed in HPV-positive cervical cancer samples (31.9%), whereas HPV-negative specimens expressed low levels of KIF20A (16.6%).…”
Section: Discussionmentioning
confidence: 99%
“…These E6/E7 oncoproteins have been shown to upregulate A3B (a major mutagenic protein) expression in HPV-induced tumorigenesis [53]. Other proteins, such as KLF13 and DGCR8, have also been implicated in HPV-induced tumorigenesis [54, 55]. In this study, aberrant KIF20A protein expression was observed in HPV-positive cervical cancer samples (31.9%), whereas HPV-negative specimens expressed low levels of KIF20A (16.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows a summary of these findings, including miRNAs that have been shown to be regulated directly by E7. Other miRNAs have been shown to be regulated by HPV but the specific contribution of E7 (vs. the other viral oncogenes) is not yet known (Martinez, Gardiner et al 2008; Wang, Wang et al 2009; Bonnet, Tatari et al 2010; McKenna, McDade et al 2010; Jung, Phillips et al 2014; Leung, Deng et al 2014; Liu, Gao et al 2014; McKenna, Patel et al 2014; Zheng, Liu et al 2015; Liu, Zhang et al 2016). Only a few of these miRNAs are yet known to have a clear impact on the viral life cycle or on cancer development.…”
Section: Micrornasmentioning
confidence: 99%
“…14 Recently, several studies have identified miR-27b-3p (also known as miR-27b) promotes cell proliferation and invasion in glioma and breast cancer, 15, 16 and blocks paclitaxel-induced apoptosis in cervical cancer. 17 MiR-27b-3p also reportedly plays a cancer-promoting role and is associated with poor prognosis in triple-negative breast cancer patients. 17 On the other hand, miR-27b-3p functions as a tumor suppressor to inhibit cells growth, tumor progression and the inflammatory response by inhibiting the expression of PPARγ in neuroblastoma.…”
mentioning
confidence: 99%
“…17 MiR-27b-3p also reportedly plays a cancer-promoting role and is associated with poor prognosis in triple-negative breast cancer patients. 17 On the other hand, miR-27b-3p functions as a tumor suppressor to inhibit cells growth, tumor progression and the inflammatory response by inhibiting the expression of PPARγ in neuroblastoma. 18 Moreover, miR-27b-3p attenuates the acquisition of cancer stem cell properties in luminal-type breast cancer by repression of ENPP1.…”
mentioning
confidence: 99%